Environmental Education Centers and local Community: The case of the Environmental Education Center in Meliti - Electra Pitoska; Margarita Trikka (European Regional Science Association (ERSA), 2012)
Environmental Education Centers have emerged more that thirty years ago. Preoccupation with the local environment can lead to a better understanding of universal problems, since local problems are always part of the universal. The trainees fully understand that their everyday choices and their general lifestyle influence the environment, even in very distant areas. The Ministry of Education in Greece included Environmental Education in the educational system, through various measures such as the establishment of Environmental Centers. The state allocated financial resources to the Environmental Centers and managed to form a small but very creative team of people to teach Environmental Education. Students' participation in programs and activities of the Environmental Centers is assessed to be rather positive. Retrospection in the bibliography of Environmental Centers in Greece shows that they are still in the sideline of the everyday school life, that only few programs are realized in every prefecture and that when realized there is no consistency or continuity. There is also no essential evaluation of Environmental Education and it is unknown how it contributes to the promotion of sustainability in a personal and in a community level. In 2011, at the place Meliti in the prefecture of Florina, a field study was organized in order to explore the role of an Environmental Center in distant areas. The Environmental Educational Center in Meliti was established in 2003. The study was carried out by questionnaires that were filled in by personal interview. The questionnaires were addressed to three target groups: High School students, local residents and teachers who work at the Environmental Center. Through the analysis of the study's findings many conclusions arise. Those conclusions concern the relation between the center and the local productive and economic fabric and also the relation between students and environment.
Keywords: 330; Environmental Education Centers; Local communities; Meliti-Florina; Greece GelI25